Akuntabilitas dalam Desentralisasi Fiskal: Tantangan dan Strategi untuk Tata Kelola Pemerintah Daerah - Retno Ridhawati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Fiscal decentralization is a cornerstone of local governance reform, aiming to enhance public service delivery and address regional disparities by granting local governments financial autonomy. This study investigates the accountability mechanisms of fiscal decentralization in Banggai Regency, focusing on the legal, managerial, and financial dimensions, alongside the role of participatory governance. The research aims to identify challenges and propose actionable strategies to optimize fiscal management at the subdistrict level. Employing a qualitative descriptive approach, the study collected data through observations, semi-structured interviews, and document analysis. The data were analyzed using the Miles and Huberman interactive model, emphasizing data reduction, display, and verification to ensure credibility and depth. The findings reveal that while fiscal decentralization has empowered local governments, its effectiveness is constrained by limited administrative capacity, weak oversight mechanisms, and low public participation. Robust accountability frameworks and innovative practices, such as e-governance platforms and participatory budgeting, were identified as critical to improving transparency and trust in local governance. This study contributes to the literature by contextualizing theoretical frameworks of fiscal decentralization within local governance practices. The insights are vital for policymakers seeking to refine fiscal policies and strengthen governance structures, with broader implications for sustainable regional development.